SAYUR SOP.COM : UPAYA PENINGKATAN KINERJA PEMASARAN - Lusianti, Dina; Nindyasari, Ratih (Research Center and Case Clearing House PPM School of Management, 2020)
The digitalisation era cannot be denied anymore. Technological progress with all its rapid development is a momentum to be able to take advantage of the use of technology to improve a better quality of life. The company can be said to have a good quality of life if the company has an increasing performance from time to time. As one of the main characteristics, marketing performance is the main focus. Therefore in order to improve marketing performance it is deemed necessary to synergize between conventional marketing and digitalization. Various opportunities can arise because of the synergy between conventional marketing and digitalization. Along with this to continue to innovate to do the best things to improve marketing performance through the E-Personal shopper approach. This research delves deeper into the use of E-Personal shopper into improving the performance of vegetable vendors who currently use conventional methods when conducting marketing.